Rehabilitation after mastectomy - Madetko, Renata; Ćwiertnia, Barbara (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Breast cancer is the most common tumor among women. In many cases it requires drastic surgical procedure, and breast amputation is an extreme experience for a woman. Psychological strain resulting from the fact of having a tumor and its location is accompanied by physical ailments. Weakness, limitation of muscular strength and scope of movement on the operated side, and lymphoedema following lymph nodes amputation are very common after mastectomy. To prevent these, a patient should be encouraged to do physical exercises both before and after the surgery. Such exercises, adapted to the patient’s abilities and health, improve dexterity of the limb on the operated side as well as efficiency of the cardiovascular and osseous systems and facilitate both keeping proper body mass and psychical state improvement. Decrease in the number of breast cancer recurrence and reduced mortality rate among physically active women compared to those with sedentary lifestyle prove that it is important that all women after breast cancer surgery undergo some form of kinesitherapy.